Predictors of Prolonged Cardiopulmonary Exercise Impairment After COVID-19 Infection: A Prospective Observational Study - Vonbank, Karin; Lehmann, Antje; Bernitzky, Dominik; Gysan, Maximilian Robert; Simon, Stefan; Schrott, Andrea; Burtscher, Martin; Idzko, Marco; Gompelmann, Daniela (Frontiers in Medicine, 2021)
Objectives: COVID-19 is a global pandemic affecting individuals to varying degrees. There is emerging evidence that even patients with mild symptoms will suffer from prolonged physical impairment. Methods: In this prospective observational study, lung function and cardiopulmonary exercise testing have been performed in 100 patients 3 to 6 months after COVID-19 diagnosis (post-CoVG). Depending on the severity of SARS-CoV-2 infection, patients were divided into asymptotic or mild to moderate (mild post-CoVG) and severe post-CoVG (hospitalization with or without ICU/NIV). Results have been compared with an age, sex and BMI matched control group (CG, N = 50). Results: Both lung function (resting) and exercise capacity (peak workload, Wpeak and peak oxygen uptake, VO2peak - % predicted) were considerably affected in severe post-CoV patients (81.7 ± 27.6 % and 86.1 ± 20.6 %) compared to the mild post-CoVG (104.8 ± 24.0 % and 100.4 ± 24.8); p < 0.01. In addition, also the submaximal exercise performance (predicted VT1/VO2peak and VT2/VO2peak) was significantly reduced in the severe post-CoVG. Multiple linear regression analyses revealed that 74 % of the variance in relative VO2peak of post-CoV patients could be explained by the following variables: lower age, male sex, lower BMI, higher DLCO, higher predicted HRpeak, lower BR and lower SaO2peak, which were related to higher relative VO2peak values. Higher NT-proBNP and lower CK values were seen in severe compared to mild post-CoV patients. Discussion: Maximal and submaximal exercise performance in patients recovering from severe COVID-19 remain still negatively affected three to six months after COVID-19 diagnosis. The presented findings reveal that impaired pulmonary, cardiac and skeletal muscle function contributed to the limitation of VO2peak in those patients, which may have important implications on rehabilitation programs.